Presence of toxigenic Clostridioides (Clostridium) difficile in edible bivalve mollusks in Spain. (July 2020) - Candel-Pérez, Carmen; Zapata-Galián, Elvira; López-Nicolás, Ruben; Ros-Berruezo, Gaspar; Martínez-Graciá, Carmen
Clostridioides difficile reservoirs other than humans are becoming increasingly recognized, and the occurrence of the pathogen in shellfish raises concern because spores can survive cooking temperature and edible bivalve mollusks are often consumed raw or poorly cooked. This study was conducted to determine the occurrence of pathogenic C. difficile in retail bivalve mollusks. The microbiological quality of samples was also checked through the isolation of Salmonella spp. and Escherichia coli . We analyzed 129 mollusk samples from different fishmongers and grocery stores in Murcia. C. difficile was isolated from 8.53% (11/129) of the mollusks investigated. Four C. difficile isolates harbored genes for the production of toxin A and B. Salmonella spp . were not isolated from any sample and E. coli was isolated from 1.55% (2/129) of the samples, in both cases in accordance with the current legal requirements for consumption. Our findings indicate that the intake of raw or poorly cooked contaminated bivalve mollusks could be a potential source of C. difficile, leading to a risk for human health.